Method effectiveness of preschoolers’ speech correction using adaptive physical education - Moga, Mykola; Zuzin, Yuri (Edelweiss Applied Science and Technology, 2024)
Purpose: To reveal the reliability of the author’s innovative method effectiveness of the 3-5 years old children speech correction with 3rd level of speech underdevelopment using adaptive physical education. 93 children of younger (3-4 years old) and middle (4-5 years old) preschool age with 3rd level of speech underdevelopment took part in the study. They were divided into two groups: experimental (48 children) and control (45 children). The formative pedagogical experiment was performed during 2022 - 2023. The research took place in specialized preschool education institutions, as well as kindergartens of the combined type in Odessa city, as well as in Dnipro city. In addition, the own experience of correctional work with such children in the Movement Rehabilitation Center (Odesa) was analyzed. According to the dynamics of general and manual praxis in the context of the 3-5 years old children speech correction with general speech underdevelopment using adaptive physical education, it can be stated that almost all indicators from the experimental groups had a statistically (P<0.05) confirmed results (improvement). Peers from control groups also had progress in indicators, but it was not statistically confirmed (P>0.05). The conducted formative pedagogical experiment made it possible to prove the innovative method effectiveness of younger and middle preschool age children speech correction with 3rd level of speech underdevelopment using adaptive physical education.